Clinical outcomes and the role of bronchoscopic intervention in patients with primary pulmonary salivary gland-type tumors. (August 2020) - Kim, Bo-Guen; Lee, Kyungjong; Um, Sang-Won; Han, Joungho; Cho, Jong Ho; Kim, Jhingook; Kim, Hojoong; Jeong, Byeong-Ho
Highlights: Primary pulmonary salivary gland-type tumors (PSGT) are rare tumors that account for less than 1.0% of all lung cancers. Surgery is the best initial treatment for PSGT. Bronchoscopic intervention may be useful as an initial treatment in patients at high clinical stage. Bronchoscopic interventions might be useful as a bridge therapy before surgery. Abstract: Objectives: Primary pulmonary salivary gland-type tumors (PSGT) are rare among all types of lung cancer. The purpose of this study was not only to evaluate the clinical outcomes and prognostic factors after treatment, but also to assess the role for bronchoscopic intervention in PSGT. Methods: We analyzed the medical data of 181 PSGT patients who were treated between 1995 and 2018. Patients were divided into three groups according to the initial treatment, as follows: surgical resection with/without adjuvant therapy including bronchoscopic intervention (surgery group, n = 116); bronchoscopic intervention without surgical resection (bronchoscopic intervention group, n = 51); and other treatments group (n = 14). A multivariable Cox proportional hazard regression analysis was used to identify the independent prognostic factors associated with overall survival (OS) and progression free survival (PFS) after the first treatment. In addition, subgroup analysis was performed according to the clinical stage. Results: Among the 181 patients, 104 (57.5%) patients were diagnosed with adenoid cystic carcinoma (ACC), 71 (39.2%) with mucoepidermoid carcinoma, and 6 (3.3%) with epithelial-myoepithelial carcinoma. In the surgery group, 21 patients underwent bronchoscopic intervention as a bridge therapy before surgery because of respiratory distress. Poor OS was associated with older age, the existence of other malignancy, higher clinical stages, larger tumor size, and non-surgical treatments. Lower PFS was associated with ACC, larger tumor size, and non-surgical treatments. The surgery group had the best OS and PFS among all treatment groups. However, there was no significant difference in the OS between the surgery and bronchoscopic intervention groups ( p  = 0.66) in patients at high clinical stages. Conclusions: Surgical resection was the best initial treatment choice. However, bronchoscopic intervention may be useful as the initial treatment in patients at high clinical stage and as a bridge therapy prior to surgery.